Study on Low-Frequency TEM Effect of Coal during Dynamic Rupture - Cheng-wu Li; Chuan Wang; Bei-jing Xie; Xiao-yuan Sun; Xiao-meng Xu (Shock and Vibration)
Dynamic loads provided by the SHPB test system were applied to coal specimens, and the TEM signals that emerged during coal rupture were recorded by the TMVT system. Experiments on coal-mass blasting rupture in excavating workface were also carried out, and the emerged TEM signal was analyzed. The results indicate that the low-frequency TEM signals were detected close to the coal specimens under high strain dynamic load applied by the SHPB, initially rising sharply and dropping rapidly, followed by a small tailing turbulence. And the field test results obtained during coal blasting process coincided with the results from the SHPB tests. Furthermore, its initial part shaped like a pulse cluster had a more pronounced tail and lasted even longer. And the generation mechanism of the low-frequency TEM effect was analyzed. It suggests that the low-frequency TEM effect of coal during dynamic rupture is contributed by the fractoemission mechanism and the resonance or waveguide effects. Because its wavelength is longer than the higher ones, the low-frequency TEM has a good anti-interference performance. That can expand the scope and performance of the coal-rock dynamic disaster electromagnetic monitoring technique.